When Religious Conservatism Intertwines with Anti-Scientism: Friday Prayers in the Time of Corona in Semarang, Indonesia - Wijayanto Wijayanto; Muhammad Adnan; Aniello Iannone; Yanwar Pribadi (Universitas Islam Internasional Indonesia (UIII), 2025)
This article discusses the implementation of Friday prayers during the early stages of the COVID-19 pandemic in Indonesia. It focuses on why Islamic preachers, mosque administrators, and religious leaders (ʿulamā) continued to hold congregational prayers despite appeals and even prohibition from the government, scientists, and Islamic organizations. By examining the contents of 67 Friday prayers’ sermons from 67 mosques in Semarang, Central Java, in-depth interviews with ʿulamāʾ, and journalistic reports, we argue that, firstly, a growing trend of religious conservatism influenced the reasons behind the performance of Friday prayers. Secondly, most Islamic preachers, mosque administrators, and religious leaders ignored scientists’ advice on appropriate COVID-19 health protocols. Finally, there was a sense of bewilderment at mosques, caused by poor communication and ambiguous messages from the government and Islamic mass organizations. All in all, these strong religious factors reflect the rapid growth of conservative forms of Islam in post-New Order Indonesia.